Conceptual Models of the Effect of Information and Communications Technology on Long-Distance Travel Demand. Issue 1 (2017) - Erhardt, Gregory D.
Rapidly evolving information and communications technology (ICT) poses a risk to the accuracy of long-distance travel (LDT) demand forecasts. The nature of this risk is multifaceted: ICT could reduce demand if people substituted virtual for physical travel, or it could serve as a complement and thereby induce more demand. This paper presents two conceptual models for better understanding the nature of those relationships. Both models start from an existing LDT model and envision how that model can be adapted to capture ICT effects, with one considering the effects explicitly and the other implicitly. When the effects of future technology are being forecast, data collected in the past or in the present, when the future technology does not exist, are inherently limited. In such situations, conceptual models such as these can be applied by using a scenario-based approach to explore a range of reasonable outcomes. This strategy can be an important tool not just for ICT, but also for understanding the risks posed by other future technologies, such as autonomous vehicles.